RENCANA STRATEGIS PENGEMBANGAN LABORATORIUM DI INSTITUT PEMERINTAHAN DALAM NEGERI KAMPUS KALIMANTAN BARAT - Verlyana Risyah; Silverius Tey Seran (Institut Pemerintahan Dalam Negeri, 2023)
This study aims to describe the strategic plan in the development of laboratories at the Institute of Domestic Government, West Kalimantan Campus. This research uses a descriptive qualitative approach, with data collection techniques namely observation, interviews, and documentation, as well as data analysis techniques through data reduction, data presentation, and conclusion drawing. This research also uses SWOT Analysis to analyze aspects of strengths, weaknesses, opportunities, and threats in the strategic plan for laboratory development and information technology. The results showed that the implementation of laboratories at IPDN West Kalimantan was not optimal due to several things, including the unavailability of qualified human resources in laboratory management, minimal supporting infrastructure, and internal educational curriculum factors that had not been compiled in an integrated manner by relevant stakeholders.